Carl Philipp Emanuel Bach (1714–1788): Six Sonatas with Varied Reprises, Wq 50 - Beghin, Tom (Evil Penguin TV and Orpheus Instituut, 2024)
Tom Beghin, clavichordDirected by Tom Beghin and Anastasios ZafeiropoulosCamera: Bo Aerts and Xin Van DammeVideo editing: Bo Aerts, with Xin Van DammeSound: Steven Maes, George Georgiev, and Lowie PeetersSound artistic supervision: Luca MontebugnoliSound editing: Tom BeghinSound mastering: Steven MaesFilmed at Koetshuis, Orpheus Instituut, Ghent, June 1–2, 2024An Orpheus Instituut and Evil Penguin TV production
Abstract:C. P. E. Bach’s Sonatas with Varied Reprises, published in Berlin, 1760, constituted a bold experiment. Throughout this opus of six Bach spelled out every repeat, integrating into the printed text his own composed variations. This practice of varying repeats normally belonged to the realm of the performer, so Bach was treading on unchartered territory, even inventing (in his own words) “a new genre.” Starting off as a service (“play this and you’ll sound as if you’re improvising”), the opus ends up a masterclass in variation. Tom Beghin, playing his own beloved clavichord (by Joris Potvlieghe, 2003), enacts the role of the keyboardist-composer who repeats himself, while never saying the same thing twice.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850